Hepatic Artery Thrombosis in Live Liver Donor Transplantation: How to Solve - a Case Report - Rodrigues, S (2014)
The decrease in the number of cadaveric donors has proved a limiting factor in the number of liver transplants, leading to the death of many patients on the waiting list. The living donor liver transplantation is an option that allows, in selected cases, increase the number of donors. One of the most serious complications in liver transplantation is hepatic artery thrombosis, in the past considered potentially fatal without urgent re-transplantation. A white male patient, 48 years old, diagnosed with hepatocellular carcinoma in chronic liver failure caused by hepatitis B virus, underwent living donor liver transplantation (right lobe). Doppler echocardiography performed in the immediate postoperative period did not identify arterial flow in the right branch, having been confirmed thrombosis of the right hepatic artery in CT angiography. Urgent re-laparotomy was performed, which consisted of thrombectomy and re-anastomosis of the hepatic artery with segmental splenic artery allograft interposition. The patient started anticoagulation and antiplatelet therapy with acetylsalicylic acid. Serial evaluation with Doppler echocardiography showed hepatic artery patency. At present, the patient is asymptomatic. One of the most devastating complications in liver transplantation, and particularly in living liver donor, is thrombosis of the hepatic artery; thus, early diagnosis and treatment is vital. The rapid intervention for revascularization of the graft avoids irreversible ischemia of the bile ducts and hepatic parenchyma, thus avoiding the need for re-transplantation.